Effect of Thickness and Thermal Annealing on Optical Properties of Sb Thin films - Hachim, Fatin (Iraqi Journal of Science, 2023)
Antimony (Sb) films are fabricated by depositing (Sb) on glass substrates at roomtemperature by the method of vacuum evaporation with thickness (0.25 and 0.51m),with rate of deposition equal to (2.77Å/sec), the two samples are annealed in avacuum for one hour at 473K. The optical constants which are represented by therefractive index (n), extinction coefficient (k) were determined from transmittancespectram in the near Infrared(2500-3500 )nm regions. The tests have been shownthat the optical energy gap increases with increasing of annealing temperature forthe two samples.